From AChE to BACE1 inhibitors: The role of the amine on the indanone scaffold. Issue 14 (15th July 2015) - Rampa, Angela; Mancini, Francesca; De Simone, Angela; Falchi, Federico; Belluti, Federica; Di Martino, Rita Maria Concetta; Gobbi, Silvia; Andrisano, Vincenza; Tarozzi, Andrea; Bartolini, Manuela; Cavalli, Andrea; Bisi, Alessandra
Graphical abstract